Real-life homeschooling : the stories of 21 families who teach their children at home - Barfield, Rhonda (Fireside, 2002)
Recounts the experiences of twenty-one families who homeschooled their children, exploring the various teaching strategies that were used and discussing why some worked and others didn't.